A dynamical systems analysis of afferent control in a neuromechanical model of locomotion. I. Rhythm generation - Spardy, Lucy E. (2011)
Locomotion in mammals is controlled by a spinal central pattern generator (CPG) coupled to a biomechanical limb system, with afferent feedback to the spinal circuits and CPG closing the control loop. We have considered a simplified model of this system, in which the CPG establishes a rhythm when a supra-spinal activating drive is present and afferent signals from a single-joint limb feed back to affect CPG operation. Using dynamical systems methods, in a series of two papers, we analyze the mechanisms by which this model produces oscillations, and the characteristics of these oscillations, in the closed and open loop regimes. In this first paper, we analyze the phase transition mechanisms operating within the CPG and use the results to explain how afferent feedback allows oscillations to occur at a wider range of drive values to the CPG than the range over which oscillations occur in the CPG without feedback and to comment on why stronger feedback leads to faster oscillations. Linking these transitions to structure in the phase plane associated with the limb segment clarifies how increased weights of afferent feedback to the CPG can restore locomotion after removal of supra-spinal drive to simulate spinal cord injury.